Evaluation and effectiveness of the ICT subject in primary schools: Kurikulum Merdeka - Aurylia Taffana (Hipkin Journal of Educational Research, 2026)
This research was motivated by concerns that the Information and Communication Technology (ICT) subject in the Kurikulum Merdeka could become an additional burden for elementary school students at the early stages of cognitive development. This study aims to evaluate the suitability and effectiveness of ICT learning implementation in elementary schools and identify challenges and improvement strategies. The method used was a descriptive qualitative approach with a case study method through semi-structured interviews with the principals of SD IT Ibnu Sina and SD IT Bahtera Nuh. The results show that ICT learning can be effective when materials and methods are tailored to students' developmental stages. Students demonstrated high enthusiasm and experienced improved digital skills and positive learning attitudes. The main obstacles faced include limited facilities and infrastructure, as well as teacher competency. This study recommends ongoing teacher training, the development of contextual materials, and improvements to learning support facilities. These findings indicate that, with appropriate support, ICT subjects can contribute to achieving the Independent Curriculum goals and strengthen students' digital competencies from an early age.   Abstrak Penelitian ini dilatarbelakangi oleh kekhawatiran bahwa mata pelajaran Teknologi Informasi dan Komunikasi (TIK) dalam Kurikulum Merdeka dapat menjadi beban tambahan bagi murid sekolah dasar yang masih berada pada tahap perkembangan kognitif awal. Penelitian ini bertujuan untuk mengevaluasi kesesuaian dan efektivitas implementasi pembelajaran TIK di sekolah dasar serta mengidentifikasi tantangan dan strategi perbaikannya. Metode yang digunakan adalah pendekatan kualitatif deskriptif dengan metode studi kasus melalui wawancara semi-terstruktur terhadap kepala sekolah di SD IT Ibnu Sina dan SD IT Bahtera Nuh. Hasil penelitian menunjukkan bahwa pembelajaran TIK dapat berlangsung secara efektif apabila materi dan metode disesuaikan dengan tahap perkembangan murid. Murid menunjukkan antusiasme tinggi dan mengalami peningkatan keterampilan digital serta sikap belajar positif. Kendala utama yang dihadapi meliputi keterbatasan sarana dan prasarana dan kompetensi guru. Penelitian ini merekomendasikan perlunya pelatihan guru yang berkelanjutan, pengembangan materi yang kontekstual, serta peningkatan fasilitas pendukung pembelajaran. Temuan ini mengindikasikan bahwa dengan dukungan yang tepat, mata pelajaran TIK dapat mendukung tercapainya tujuan Kurikulum Merdeka dan memperkuat kompetensi digital murid sejak dini. Kata Kunci: kompetensi digital; Kurikulum Merdeka; pembelajaran TIK; sekolah dasar